Effect of foliar nano urea plus combined with split nitrogen application on growth, physiological parameters and grain yield of finger millet (Eleusine coracana L.) - Akchaya, Kalaimegam; Thirukumaran, Kanthan; Manivannan, Venkatesan; Kannan, Pandian; Deepika, Rajendran; Vanathi, Durai; Vellaikumar, Sampathrajan; Vijayalakshmi, Dhashnamurthi; Madhavan, Gnanasekaran; Harini, Harishma Veerappan Prithiviraj (Plant Science Today, 2026)
Nano-fertilizers are gaining attention as a sustainable strategy to optimize physiological performance and crop productivity. A field experiment was conducted during the summer and rabi seasons of 2024 at Tamil Nadu Agricultural University (TNAU), Coimbatore, to evaluate the effect of nano urea plus (NUP) on growth, physiological parameters and grain yield of transplanted finger millet. Twelve treatment combinations with varying nitrogen levels (recommended dose of fertilizer (RDF) and organic sources) with foliar NUP (0.75 %) sprays at tillering and panicle-initiation stages were evaluated. Nitrogen fertilization integrated with NUP significantly enhanced crop vigour, canopy development and biomass accumulation. At the final growth stage, 100 % RDF + one NUP spray (T₁) improved plant height by 35 %, leaf area index (LAI) by 60 %, normalized difference vegetation index (NDVI) by 35 % and growth indices-crop growth rate (CGR), relative growth rate (RGR) and absolute growth rate (AGR)-by 50 % compared to the absolute control, contributing to superior physiological efficiency. The same treatment also produced the highest grain yield (2588 and 2555 kg ha-1) in both seasons. This performance was statistically comparable to 75 % RDF with two NUP sprays and 100 % RDF alone. These findings indicate that foliar application of NUP with optimal nitrogen application can strengthen nutrient-use efficiency and support sustainable nutrient management in finger millet production.